Investigação da Atividade Neuroprotetora de Polissacarídeos Sulfatados de Algas Marinhas em Modelos in vitro de Neuroinflamação e in vivo de Parkinson - Frota, Annyta Fernandes (2020)
The marine environment is known as a rich source of chemical compounds with numerous beneficial health effects. Among marine organisms, we highlight marine algae. Although they have been recognized as valuable sources of bioactive compounds, they are still a little explored resource. Currently, several lines of studies have provided information on biological activities and neuroprotective effects of seaweed, including antioxidant, anti-neuroinflammatory and neuronal death inhibition activity. Therefore, seaweed has great potential to be explored in neuroprotection as part of pharmaceutical, nutraceutical and functional foods. The species of the red algae Gracilaria cornea, Gracilaria birdiae and Hypnea pseudomusciformis, present themselves as a natural source still little explored as potential bioactive. Its sulfated polysaccharides (SP), of the type agarana and carrageenan, already have a characterized structure and biological effects reported in the literature. Thus, the present study aimed to evaluate the neuroprotective effects of SP and possible mechanisms of action in a model of glial neuroinflammation in vitro and neurodegeneration in vivo. In order to assess aminochrome- induced neuroinflammation in vitro, SP (10 μg/mL) were incubated in glial cells for 24 h. For the investigation of the neuroprotective potential in vivo, rats received nigrostriatal injection of the neurotoxin 6-hydroxidopamine (6-OHDA), and subsequent sub-chronic treatment, orally, with SP (0.3, 3.0 and 30 mg/Kg) for 14 consecutive days. One hour after the last treatment, the animals were submitted to neurobehavioral analysis. The brain areas were dissected and used for neurochemical and transcriptional analyzes. SP of the algae G. cornea, G. birdiae and H. pseudomusciformis, promoted a neuroprotective effect in glial cells, induced microglial and astrocytic proliferation, through the modulation of neurotrophic factors. In addition, they promoted a neuroprotective activity in vivo, through reduced glutathione induction, reduced levels of lipid peroxidation and nitrite, and modulation of transcriptional pathways in rat striatum, returning locomotor activities to normal conditions. Thus, the present study presents new biotechnological perspectives of SP of seaweed and suggests new neuropharmacological implications for the use of the G. cornea, G. birdiae and H. pseudomusciformis galactans.